2022
DOI: 10.3390/jcm11102936
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Phenotypes in Early Multiple Sclerosis: Appraisal of Phenotype Frequency, Progression and Test Sensitivity

Abstract: Working memory (WM) impairments are common and debilitating symptoms of multiple sclerosis (MS), often emerging early in the disease. Predominantly, WM impairments are considered in a binary manner, with patients considered either impaired or not based on a single test. However, WM is comprised of different activated subcomponents depending upon the type of information (auditory, visual) and integration requirements. As such, unique WM impairment phenotypes occur. We aimed to determine the most frequent WM phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Only the immediate recall sessions on the test are included in the BICAMS battery. According to the current literature, these sessions may assess some aspects of VWM [ 40 ]. The examiner read out a list of 16 goods that the participant should hypothetically buy from the supermarket on a Monday.…”
Section: Methodsmentioning
confidence: 99%
“…Only the immediate recall sessions on the test are included in the BICAMS battery. According to the current literature, these sessions may assess some aspects of VWM [ 40 ]. The examiner read out a list of 16 goods that the participant should hypothetically buy from the supermarket on a Monday.…”
Section: Methodsmentioning
confidence: 99%
“…As such, this phenotype may represent the earliest onset of visual processing changes that will potentially worsen to clinically evident visual processing deficits over time. Indeed, Clough et al [42] recently examined the evolution of working memory phenotypes in early MS and found that ocular motor assessment detected worsening cognitive visual processing over a two-year period despite no changes in performance on standard neuropsychology evaluation.…”
Section: Early Visual Changes Phenotypementioning
confidence: 99%